Aplikasi Media Inspirasi Berbasis Web dan Android - Sulistya Ferryanto; Yulia Yulia; Andreas Handojo (Jurnal Infra, 2016)
Nowadays application for storing images and videos have been very easy to find. Videos and images can be found on social media appplications. However, images and videos are not too restricted to be submitted by member in social media applications. It makes the user rather difficult to find videos or images that are inspiring. In general, inspiration media application only for showing videos or images. Besides that, there are applications that can only be accessed on the website or Android. Inspiration media application that already exist can be only inserted by admin so that the user can not upload video or image that the user want.MPV (Motivation Photo and Video) application made for help the user to find application that only have inspiration content more easy. That is because this application only save video or image with these categories such as motivation, work, relation, spiritual, and health. This application gives permission for member to upload video and image that the user want. Member can make quote as they want. Videos or images on application can be shared to others by Facebook. This application also can send notification to member.Based on the test result, the conclusion is this application that made on Android can run well on Android version 4.4 (Kitkat) to Android version 5.0 (Lollipop). This application also can upload video, upload image, send notification to member about the latest video or image, share image and video on Facebook and make a personal quote.